Xinjiang between the globes: The Ottomans in the making of modern Xinjiang - Kuzuoğlu, Uluğ. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
This thesis examines the period from the 1860s to 1934 in disclosing the Ottoman, and later the Turkish, influence in Xinjiang. In doing so, this study has two main purposes. The first one is to use the nascent “global history” narrative which seeks to understand the influence of the non-West on the non-West, and opposes the Eurocentric approach to history that views modernity solely as a Western construction. The second purpose is to re-evaluate the ideologies of Pan-Islamism and Pan-Turkism from the local context of Xinjiang. Conventionally, there are two viewpoints with regard to these ideologies. The first one is the viewpoint of the right-wing intellectuals, who regard them as ever-existing ideologies that may be realized once the socio-political conditions are ripe. The second viewpoint opposes the first one, and observes these ideologies as the futile struggle of the Ottoman Empire which is about to get perished from the face of history. The Chinese literature on these ideologies is also problematic, for they are merely regarded as the main source of “Xinjiang separatism.” This study opposes these viewpoints, and argues that the Pan-Islamist and Pan-Turkist ideologies of the Ottoman Empire did not have a purpose of liberating Xinjiang from Chinese rule, at least until 1918. The 1930s, on the other hand, witnessed both a socio-political and an ideological transformation in Xinjiang, and the Pan-Turkism of this period was inherently different from the Ottoman period. Therefore, in observing the historical processes these two ideologies have followed, this thesis argues that it is not possible to observe these processes as indivisible components of the same linear line.